Bloody Foundation? Ethical and Legal Implications of (Not) Removing the Equestrian Statue of Theodore Roosevelt at the American Museum of Natural History - Marber, Sinclaire Devereux (The Columbia Journal of Law & the Arts, 2019)
On October 26, 2017, protestors calling themselves the Monument Removal Brigade (“MRB”) splashed red paint on the base of a statue of Theodore Roosevelt outside the American Museum of Natural History (“AMNH,” “Museum,” or “Natural History Museum”) in New York City as a form of public protest art. This 1939 sculpture by American artist James Earle Fraser (the “Equestrian Statue of Theodore Roosevelt” or “Equestrian Statue”) portrays the twenty-sixth president of the United States sitting upon a horse, flanked on either side by a standing African man and Native American man intended to represent their respective continents. On its anonymous blog, MRB called for the statue’s removal and claimed, “[t]he true damage lies with patriarchy, white supremacy, and settler-colonialism embodied by the statue.” The Mayoral Advisory Commission on City Art, Monuments, and Markers (the “Commission”) conducted a study of controversial monuments on public land in New York City and was unable to agree on an appropriate fate for the AMNH statue; for this reason, it has remained in place for the time being. In July of 2019, the AMNH opened a special exhibition entitled Addressing the Statue. This AMNH protest occurred within a larger national conversation about the place of public monuments, especially those commemorating leaders of the Confederacy. But the current debate often lacks scholarly rigor, with little consideration of the history, intention, or artistic merit of the monuments in question, or the federal, state, local, and administrative laws governing their removal or modification. This Article draws upon the disciplines of art history, museum studies, and the law to contextualize the AMNH Equestrian Statue and expand upon the Commission’s and AMNH’s analyses to develop a suggested framework for considering controversial monuments in the future.